Weakly nonlinear oscillatory convection in a viscoelastic fluid saturated porous medium with throughflow and temperature modulation - Kiran, Palle; Narasimhulu, Y.; Manjula, S.H. (Zielona Góra: Uniwersytet Zielonogórski)
The effect of vertical throughfow and temperature modulation on a viscoelastic fluid saturated porous medium has been investigated. The amplitudes of temperature modulation at the lower and upper surfaces are considered to be very small and the disturbances are expanded in terms of power series of amplitude of convection.
Keywords: throughflow; temperature modulation; weak nonlinear theory; complex Ginzburg-Landau model